2016
DOI: 10.1080/03630242.2016.1170094
|View full text |Cite
|
Sign up to set email alerts
|

Partner violence victimization and unintended pregnancy in Latina and Asian American women: Analysis using structural equation modeling

Abstract: Intimate partner violence (IPV) is a pervasive public health problem in the U.S., affecting nearly one in every three women over their lifetimes. Using structural equation modeling, we evaluated the association between IPV and unintended pregnancy, mediated by condom use and perceived spousal/partner support among Latina and Asian women. Data came from the 2002-2003 National Latino and Asian American Study (NLAAS). The analysis was restricted to married or cohabiting female respondents aged 18+ years (n = 1,59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…A similar finding from the U.S also revealed that the significant association between IPV and unintended pregnancy, where abused women were twice as likely as non-abused women to have had an unintended pregnancy, was not mediated by condom use. In this study, condom use had a positive association with unintended pregnancy and IPV had a negative association with condom use but both associations were not significant [ 51 ]. While some previous evidence has shown that IPV is associated with contraception use [ 18 20 ], in this study the association between IPV and contraception use was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding from the U.S also revealed that the significant association between IPV and unintended pregnancy, where abused women were twice as likely as non-abused women to have had an unintended pregnancy, was not mediated by condom use. In this study, condom use had a positive association with unintended pregnancy and IPV had a negative association with condom use but both associations were not significant [ 51 ]. While some previous evidence has shown that IPV is associated with contraception use [ 18 20 ], in this study the association between IPV and contraception use was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…In another study of women aged 18 or older, married or cohabitating Latina and Asian women, only those who experienced IPV, were twice as likely to experience a UIP relative to women who were not exposed to IPV. 32 Despite emerging work on the impact of RC on UIP, studies to date have not assessed the combined impact of race/ethnicity and RC/IPV on risk for UIP.…”
Section: Introductionmentioning
confidence: 99%
“…Among Asian women, physical violence experience included unwanted pregnancy by a husband/partner and imprisonment of self or husband. In general, a batterer is more likely to have control over a victim’s sexuality/life and engage in sexual risk-taking behaviors (e.g., unprotected sex), which elevates the risk of unwanted pregnancy (Cha, Masho, & Heh, 2017; Coker, 2007). Reversely, women whose partner does not want the current pregnancy are at more than 3 times greater risk of being a victim of physical violence relative to their counterparts who want the pregnancy (Chu, Goodwin, & D’Angelo, 2010).…”
Section: Discussionmentioning
confidence: 99%